2016
DOI: 10.3171/2015.3.jns142212
|View full text |Cite
|
Sign up to set email alerts
|

Neopterin plasma concentrations in patients with aneurysmal subarachnoid hemorrhage: correlation with infection and long-term outcome

Abstract: A neurysmAl subarachnoid hemorrhage (aSAH) is a subtype of stroke associated with high rates of mortality and morbidity. Fifteen percent of patients die before arriving at a hospital, and 25% of deaths occur within the first 24 hours. 34 Among the survivors, 30% will develop a long-term delayed neurological deficit that will affect their quality of life. 21,32The long-term outcome partially depends on early diagnosis and management.1,12 Therefore, if an aneurysm is detected by CT in a patient with aSAH, invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
10
1
Order By: Relevance
“…In a previous study, we showed also that NP correlates with the progression of infection from three days after hospitalization [14]. Nevertheless, present results showed that this discrimination capacity was not effective at the admission to the hospital, making from SAA an earlier and most accurate infection marker than NP.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In a previous study, we showed also that NP correlates with the progression of infection from three days after hospitalization [14]. Nevertheless, present results showed that this discrimination capacity was not effective at the admission to the hospital, making from SAA an earlier and most accurate infection marker than NP.…”
Section: Discussioncontrasting
confidence: 59%
“…However, for aSAH patients, no blood biomarkers are available in clinical practice. We recently showed that neopterin (NP) and serum amyloid A (SAA) could be promising predictive markers of infection as their plasma concentrations were significantly higher in patients developing infection during hospitalization compared to those who did not [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In the primary and secondary damage process of neural function, neurons and glial cells within the nervous tissue will rupture and cause the release of many marker molecules from the cytoplasm into outside of the cells, which cross through the damaged blood brain barrier and enter into the blood circulation [15][16]. S100β and NSE are the marker molecules positioning in neurons, the former is a kind of calcium-binding protein, and it is closely related to the regulation of Ca2+ homeostasis within neurons and the regulation of cytoskeleton elements; the latter is the key enzyme of glycolysis function way in neurons, and it is of great significance to the neuron ATP production and function [17].…”
Section: Discussionmentioning
confidence: 99%
“…The damage of blood brain barrier will lead to the release of OPN into blood circulation [18]. S100β and NSE are mainly expressed in the neuron cells, while the former one participates in the regulation of intracellular calcium homeostasis and the dynamic change of cytoskeletal components, and the latter one gets involve with the regulation of energy metabolism in the cell [19][20][21]. GFAP and MBP are mainly expressed in the neurogliocyte which participates in the formation of cytoskeleton and the regulation and control of cell membrane stability [22,23].…”
Section: Volume Of Edema (Ml)mentioning
confidence: 99%